Solving an integral equation via intuitionistic fuzzy bipolar metric spaces - Mani, Gunaseelan; Joseph Gnanaprakasam, Arul; Kausar, Nasreen; Munir, Muhammad; Khan, Salma; Ozbilge, Ebru (Decision Making: Applications in Management and Engineering, 2023)
In this paper, we introduce the notion of intuitionistic fuzzy bipolar metric space and prove fixed point theorems. Our results are an extension or generalization of results proved in the literature. The derived results are substantiated with suitable examples and an application.